CURAHAN WAKTU WANITA TANI DAN KONTRIBUSINYA TERHADAP PENDAPATAN KELUARGA DI DESA MUARA LEMBU KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI (STUDI KASUS BURUH TANI PERKEBUNAN KARET) - Irma Puspita Ayu Harahap; Rosnita '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to analysis outpouring time of women farm workers in family and factor-factor that effect to working hours, to knows role of women farm workers in decision-making in the family. Analysis contribution income of women farm workers toward family’s income. The research used a survey of random sampling method and sampling as many as 36 ​​samples. Analysis of the data using Ordinary Liest Square (OLS) and analysis of income. The results showed that the average working hours of economic is high at 5,62HKP/day and compared to average of non economic working hours of women are only 4,74 HKP/day. Contribution income of woman farm workers in rubber plantation toward family’s income is 40,00%, and she is capable can in helping family economy. . Keywords: Outpouring of time, family income